A novel method for assessment of fragmentation and beam-material interactions in helium ion radiotherapy with a miniaturized setup. (October 2017) - Gallas, Raya R.; Arico, Giulia; Burigo, Lucas N.; Gehrke, Tim; Jakůbek, Jan; Granja, Carlos; Tureček, Daniel; Martišíková, Maria
Highlights: Development of a method for assessment of interactions between He-ions and materials. Small semiconductor pixel-detectors enable ion type identification and tracking. Speed, flexibility and small size can facilitate the gain of large amounts of data. Measured fractions of He- and H-ions behind irradiated PMMA targets are reported. The comparison to MC-simulations shows that the models in Geant4 can be improved. Abstract: Radiotherapy with protons and carbon ions enables to deliver dose distributions of high conformation to the target. Treatment with helium ions has been suggested due to their physical and biological advantages. A reliable benchmarking of the employed physics models with experimental data is required for treatment planning. However, experimental data for helium interactions is limited, in part due to the complexity and large size of conventional experimental setups. We present a novel method for the investigation of helium interactions with matter using miniaturized instrumentation based on highly integrated pixel detectors. The versatile setup consisted of a monitoring detector in front of the PMMA phantom of varying thickness and a detector stack for investigation of outgoing particles. The ion type downstream from the phantom was determined by high-resolution pattern recognition analysis of the single particle signals in the pixelated detectors. The fractions of helium and hydrogen ions behind the used targets were determined. As expected for the stable helium nucleus, only a minor decrease of the primary ion fluence along the target depth was found. E.g. the detected fraction of hydrogen ions on axis of a 220 MeV/u 4 He beam was below 6% behind 24.5 cm of PMMA. Monte-Carlo simulations using Geant4 reproduce the experimental data on helium attenuation and yield of helium fragments qualitatively, but significant deviations were found for some combinations of target thickness and beam energy. The presented method is promising to contribute to the reduction of the uncertainty of treatment planning for helium ion radiotherapy.